Modeling and Performance Characteristics of Nanofiltration by DSPM and ARX Model - Deepak, D.; Arthanareeswaran, G. (Journal of Applied Membrane Science & Technology, 2017)
The DSPM (Donnan Steric Pore Model) is integrated with osmotic pressure to develop nanofiltration modeling. The new model establishes the relation between the pressure across the membrane to the concentrations of permeate and retentate at a particular solute concentration in the feed. The model is successfully tested against the experimental data. We also developed the nanofiltration modeling with ARX (Auto Regressive Exogeneous), a type of black box model. The data for modeling is obtained by simulation of the first principle model. With the help of identification toolbox, an ARX model is developed considering pressure across the membrane as input variable (manipulated variable) and percentage rejection as output variable (control variable). The model is validated against a data subset used for estimation of model. However, the models are sustained only at low feed concentrations. The model output data are compared to the actual output data and calculate the mean square errors (MSE). The obtained residuals are well satisfactory in the range of 0.99. Hence, the derived modeling sustains for nanofiltration and its control operations.